FOX Indonesia's Role in SBY-Boediono's Win in the 2009 PILPRES - Muslahudin Muslahudin (The International Journal of Politics and Sociology Research, 2021)
Marketing science as a discipline that develops in the business world is assumed to be useful for political institutions. The methods and approaches contained in marketing science can help political institutions to bring political products to their constituents and society at large. Political institutions can use marketing methods in preparing political products, distributing political products to the public and ensuring that their political products are superior to competitors. Political marketing has become a phenomenon, not only in political science, but also raises various questions for marketers who have been used to it in the context of the business world. The 2009 elections, both legislative and presidential elections, provide evidence that political marketing plays an important role in the success of a candidate. both legislative and presidential candidates. The victory of the Democratic Party is the fruit of the political branding carried out by SBY, as chairman of the advisory board. SBY-Boediono's victory cannot be separated from Fox Indonesia's role as a drafter for SBY's personal branding. The 2009 presidential election is different from the previous one, currently the connection between the legislative and presidential elections is very strong. SBY's victory in the 2009 presidential election, apart from the political marketing support carried out by Fox Indonesia, either directly or indirectly, such as financing survey institutions to form opinions, starting from SBY's victory, to the one-round election, turned out to be successful in influencing the voting public. This is inseparable from the trend of using political consulting institutions for parties who want to run for leadership candidates at various levels of government, even up to the president. The existence of political consultants in Indonesia has brought about a change in the world of politics in the archipelago.